(untitled) (Biological Sciences - PJSIR, 2024)
Diafenthiuron is a thiourea derivative propesticide widely used in agriculture and forestry, involved in inhibition of oxidative phosphorylation and interrupts the mitochondrial ATP synthesis of the pest. Because there is no research regarding the toxicological effects of this chemical on non-target species. Hence the present study aim to assess the acute toxicity of this insecticide on rabbits (Oryctolagus cuniculus). A total of 48 rabbits were categorized into four groups, with 12 rabbits in each group. The groups were named as T0 (control), T1 (low dose), T2 (medium dose) and T3 (high dose). Rabbits in groups T1, T2 and T3 received oral administration of diafenthiuron at doses of 500 mg/Kg, 1000 mg/Kg, and 1500 mg/Kg, respectively which is based on their body weight. This administration continued for a period of 45 days. The T0 group served as the control group. Blood samples were collected at 15th, 30th and 45th day of experiment and analyzed for blood profile, hepatorenal performance and immunological analysis. Our results indicated that complete blood count was significantly (P 0.05) reduced, except for platelets level which were significantly higher in dosage dependent groups as compared to control group. Furthermore, antibody titer test for immunity against Rabbit Hemorrhagic Disease (RHD) virus was also reduced in dosage dependent groups. However, hepatorenal parameters (bilirubin, alanine aminotransferase, aspartate transaminase, alkaline phosphatase, urea and creatinine) were significantly elevated upon exposure to the higher dosage of pesticide. Our study concluded that diafenthiuron has strong potential to cause toxicity even at sub lethal doses which in turn, affects the non-target organisms including human beings. Therefore, alternative ways must be used to avoid the accumulation of this pesticide in the environment.